Indigenous Resource Management System in Selected Backwater Stake net Fisheries of Kerala - Thomas, Saly N.; Archana, G.; Edwin, Leela (Fishery Technology, 2019)
Application of indigenous knowledge is commonamong the traditional fishers operating indigenousfishing systems. Stake net is an important gearoperated along the backwaters of Kerala. Stake netfishers follow many traditions in the fabrication,operation and maintenance of the fishing unit.Lunar periodicity based fishing operation and paadusystems envisage resource conservation throughcontrol of fishing effort. The fishing canoe and thegear are protected against biodegradation using ecofriendlynatural protective coatings thereby protectingthe biota from the ill-effects of synthetic dyesand chemical preservatives.